Delegated Legislation Making Models in Indonesia within 1999-2012 - Fitriani Ahlan Sjarif (Universitas Negeri Semarang, 2023)
Based on the UUD 1945, delegated legislation in Indonesia is Government Regulations made by the President. The making of delegated legislation from 1999 to 2012 has shown some development in how delegated legislation is made. Therefore, this article shows three traditional models of delegated legislation in Indonesia between 1999 to 2012 that are different from the stipulations provided within the UUD 1945. Practice shows that there are 3 traditions of delegation legislation making models in Indonesia. Such tradition is not in accordance with the provisions in the Indonesian constitution. Therefore, it is necessary to control the delegation of Laws in Indonesia by selecting government regulations as delegated legislation.